CT Measured Psoas Density Predicts Outcomes in Trauma - Yoo, Taehwan (Surgery, 2017)
BACKGROUND: Age-related loss of muscle mass and function (sarcopenia) is linked to poor outcomes after surgery and trauma. Here we evaluate CT measured psoas muscle density and area using quick and simple tools available to the beside clinician. We hypothesize these measures will predict poor outcomes after blunt traumatic injury. METHODS: We conducted a retrospective cohort study of patients ages ≥ 45 years in the Ohio State University Trauma Registry in 2008 that received a CT abdomen/pelvis with intravenous contrast. Psoas Index (PI) and Hounsfield Unit average calculation (HUAC) were measured at the L3 level. 90-day mortality, complication, length of stay ≥ 7 days, dependent discharge were compared to PI and HUAC. RESULTS: 151 patients met inclusion criteria. Patients were stratified into interquartile ranges based either on PI or HUAC values. After adjustment with sex-specific cutoffs, the lowest interquartile range of PI was associated with 90-day mortality (RR 5.95, p < 0.008) but did not reach significance in other outcomes. The lowest interquartile range of HUAC was associated with 90-day mortality (RR 5.95, p < 0.008) length of stay ≥ 7 days (RR 1.63, p = 0.048), complication risk (RR 2.30, p = 0.002), and dependent discharge 2.14, p = 0.015). CONCLUSION: Psoas muscle density is a significant predictor of poor outcomes after traumatic injury. This objective, quick, and readily available measure of sarcopenia can identify patients requiring aggressive nutritional and physical therapy to improve prognosis, prevent recurrent traumatic injury, and aid in discharge planning.